Imaging Features of Urachal Cancer: A Case Report - Chen, Xiaoyan; Kang, Chunsong; Zhang, Mingxia (Frontiers in Oncology, 2019)
Urachal adenocarcinoma originates from the space of Retzius. It is a rare but aggressive neoplasm. Typical imaging findings of urachal cancer are difficult to find; this report provides an ultrasonographic (US) and computed tomographic (CT) description of the above. We present a case of a 45-year-old male patient presenting with painless hematuria of 1 week's duration and display the US and CT images. Imaging shows: (1) a solid, ill-defined, irregularly shaped mass invading the bladder wall located between the dome of the bladder and the abdominal wall, and which underwent significant enhancement; (2) hypo-echoic, heterogeneous echopattern with some calcifications and (3) patchy and short-line blood flow signals within the mass. Final histopathology confirmed urachal adenocarcinoma.